2022
DOI: 10.3389/fneur.2022.834003
|View full text |Cite
|
Sign up to set email alerts
|

Procedural and Methodological Quality in Preclinical Stroke Research–A Cohort Analysis of the Rat MCAO Model Comparing Periods Before and After the Publication of STAIR/ARRIVE

Abstract: The translation of preclinical stroke research into successful human clinical trials remains a challenging task. The first Stroke Therapy Academic Industry Roundtable (STAIR) recommendations for preclinical research and several other guidelines were published to address these challenges. Most guidelines recommend the use of physiological monitoring to detect the occurrence of undesired pathologies such as subarachnoid hemorrhage and to limit the variability of the infarct volume and–therefore-homogenize the ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 46 publications
0
3
0
Order By: Relevance
“…In line with experimental ischemic stroke experiments, sophisticated neurovascular monitoring such as CBF and intracerebral pressure measurements plays a crucial role in detecting the severity of the induced pathology while ruling out associated complications (such as ischemia). 32 …”
Section: Discussionmentioning
confidence: 99%
“…In line with experimental ischemic stroke experiments, sophisticated neurovascular monitoring such as CBF and intracerebral pressure measurements plays a crucial role in detecting the severity of the induced pathology while ruling out associated complications (such as ischemia). 32 …”
Section: Discussionmentioning
confidence: 99%
“…3,12 Preclinical studies have shown that inhibiting inflammation both locally and systemically can reduce tissue damage and improve neurological outcome following ischemic stroke. [13][14][15] However, these studies have not led to translation to the human population for a number of reasons, including a lack of rigor and reproducibility in preclinical experimental stroke research, 16,17 lack of delivery of the therapeutic to the infarct and ischemic penumbra, 18,19 and the unknown optimal treatment window following ischemia and reperfusion, 20 as well as many technical factors. The formation, and subsequent modifications, of the Stroke Therapy Academic Industry Roundtable (STAIR) guidelines aim to increase translation of stroke therapeutics to the patient population by correcting for many of the technical limitations of prior studies.…”
Section: Introductionmentioning
confidence: 99%
“…There are numerous reasons for translational failure in preclinical stroke research conditioned by the experimental setting itself, such as the generation of a plausible hypothesis, the methodological quality of the experimental procedure and the analysis of the results (ideally double-blinded). In order to improve the quality of preclinical studies, the STAIR (Stroke Therapy Academic Industry Roundtable) and ARRIVE (Animal Research: Reporting of in vivo Experiments) guidelines were published [5, 6]. Among the recommendations described, the importance of including a sham group stands out [7].…”
Section: Introductionmentioning
confidence: 99%